THE ROLE OF BETA-BLOCKERS IN THE TREATMENT OF CARDIOVASCULAR DISEASES IN PREGNANT WOMEN - R. I. Striuk; Ya. V. Brytkova (Столичная издательская компания, 2015)
Highly selective β-adrenoblockers (β-AB) are used in pregnant women with cardiovascular diseases (arterial hypertension, arrhythmia, Marfan syndrome, hypertrophic cardiomyopathy). β-AB fall into the category C according to safety classification of Food and Drug Administration (US FDA). Their prescription in different clinical situations meets the principle of "risk-benefit". Fetus and newborn status should be monitored because β-AB can cause bradycardia, hypoglycemia, apnea and metabolic disorders. The risk of these side effects is extremely low, while β-AB clinical efficacy is high.